Transforming Growth Factor-β Protects against Inflammation-Related Atherosclerosis in South African CKD Patients - Hassan, Muzamil Olamide (Int J Nephrol, 2018)
BACKGROUND: Transforming growth factor-β (TGF-β) may inhibit the development of atherosclerosis. We evaluated serum levels of TGF-β isoforms concurrently with serum levels of endotoxin and various inflammatory markers. In addition, we determined if any association exists between polymorphisms in the TGF-β1 gene and atherosclerosis in South African CKD patients. METHODS: We studied 120 CKD patients and 40 healthy controls. Serum TGF-β1, TGF-β2, TGF-β3, endotoxin, and inflammatory markers were measured. Functional polymorphisms in the TGF-β1 genes were genotyped using a polymerase chain reaction-sequence specific primer method and carotid intima media thickness (CIMT) was assessed by B-mode ultrasonography. RESULTS: TGF-β isoforms levels were significantly lower in the patients with atherosclerosis compared to patients without atherosclerosis (p<0.001). Overall, TGF-β isoforms had inverse relationships with CIMT. TGF-β1 and TGF-β2 levels were significantly lower in patients with carotid plaque compared to those without carotid plaque [TGF-β1: 31.9 (17.2 – 42.2) versus 45.9 (35.4 – 58.1) ng/ml, p=0.016; and TGF-β2: 1.46 (1.30 – 1.57) versus 1.70 (1.50 – 1.87) ng/ml, p=0.013]. In multiple logistic regression, age, TGF-β2, and TGF-β3 were the only independent predictors of subclinical atherosclerosis in CKD patients [age: odds ratio (OR), 1.054; 95% confidence interval (CI): 1.003 – 1.109, p=0.039; TGF-β2: OR, 0.996; 95% CI: 0.994–0.999, p=0.018; TGF-β3: OR, 0.992; 95% CI: 0.985–0.999, p=0.029). TGF-β1 genotypes did not influence serum levels of TGF-β1 and no association was found between the TGF-β1 gene polymorphisms and atherosclerosis risk. CONCLUSION: TGF-β isoforms seem to offer protection against the development of atherosclerosis among South African CKD patients.